KEBIJAKAN TERHADAP KESEJAHTERAAN MASYARAKAT LANSIA JEPANG YANG BERORIENTASI PADA MODEL PEMBERDAYAAN KOMUNITAS - Yesy Tri Cahyani (LINGUA : JURNAL ILMIAH, 2022)
Abstract This article provides a brief overview of the situation of the elderly in Japan, including demographic and social changes in Japan, policy direction, and empowerment-oriented community development model. Through human security approach: protection and empowerment, government retain the primary role and responsibility for ensuring the survival, livelihood and dignity of their citizens, and requires greater collaboration and partnership among regional organizations and civil society. The human security approach, is more than an exercise in joint programming. This approach is people-centered. It considers the broad range of conditions that threaten the survival, livelihood, and dignity of people and their communities particularly those who are most vulnerable (UN Commissions of Human Security, 2010). In this case is elderly people. Policy direction designed to address elderly related issues. The potential of empowerment-oriented community development intervention strategies to decrease the gap between available institutional and formal community-based services and the needs of the elderly and their families in their efforts to meet late life challenges. The policies and programs are imitable for countries like Indonesia, where there is no substantial policies and programs for caring the elderly. We can learn various experiences from Japan both in the approach of protection (policy direction) and empowerment (collaboration and partnership) programs.